(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Distributed software systems have undergone significant architectural evolution over the past two decades. Microservices architecture emerged as a response to the limitations of monolithic and service-oriented systems, but with increasing scale and organizational complexity, new challenges related to manageability, evolvability, and architectural integrity have emerged. This article examines the evolution of distributed system architectures from microservice approaches to the concept of adaptive modular platforms. It analyzes the architectural, organizational, and technological factors driving this transition, as well as the role of modularity, contracts, and dynamic adaptation in modern software ecosystems.